The Incidence and Nature of Consistency Exceptions. - Neumann, Frederick L. (The Accounting Review, 1969)
The purpose of this study was to determine the incidence of reported changes in the consistent application of generally accepted accounting principles and practices, the nature of such changes, and their materiality. For a sample of 300 corporations chosen from Fortune's 500 and the New York Stock Exchange, changes in the principles of consolidation, the methods of computing depredation, and valuing inventory were found to be the chief reasons for auditors' qualifications during the nine years, 1955-1963. In general, there was relatively little concentration of qualifications for consistency among companies, industries, or CPA firms–either in total number, category, or year. As might be expected, more of the changes resulted in increasing reported net income than in decreasing it. The striking finding, resulting from the examination of the materiality of the reported changes was the predominance of those with an immaterial effect on net income. Possible "obvious" explanations were examined and found to be unsatisfactory. In response to Professor McCosh's admonition, it would appear from the data reported above that, if anything, accountants are overly zealous in disclosing consistency changes though they may not be as diligent in reporting the effects on net income. But, can readers of financial statements assume that this standard of reporting changes with little or no effect on net income is held by all accountants and is applied uniformly? This question will require further study.